Pathophysiology of Emphysema - Steven Jonathan; Triya Damayanti; Budhi Antariksa (Jurnal Respirologi Indonesia, 2019)
Pulmonary emphysema is part of pathological condition in chronic obstructive pulmonary disease (COPD) which is characterized by lung parenchymal destruction. Morphology classification of emphysema had been made according to histologic structure in pathology. There were some causes known to be the culprit of emphysema; one that caught most attention is protease-antiprotease activity from cigarette smoke exposure. Destructive effect of emphysema gives disturbance of lung function in expiration (obstruction). The primary mechanism is elastic recoil reduction which causes air trapping, lung volume increase, lung compliance increase and airways that is susceptible to collapse. Hyperinflation in emphysema causes some disadvantages which complicate inspiration and give a dyspnea sensation. Equal pressure point drop in emphysema happens because of elastic recoil reduction. This drop may cause early airway closure. (J Respir Indo 2019; 39(1): 60-9)